FINE ROOT BIOMASS OF ERICA TRIMERA (ENGL.) ALONG AN ALTITUDINAL GRADIENT ON BALE MOUNTAINS, ETHIOPIA - Worku, Abebe; Fetene, Masresha; Zewdie, Solomomn; Assefa, Yoseph (International Journal of Research -GRANTHAALAYAH, 2019)
Fine roots biomass of Erica trimera was investigated at three altitudinal levels, i.e. 3000, 3300, and 3500 masl across three depth classes (0-10, 10-20, and 20-40 cm) for each of the four seasons of Bale Mountains by using sequential soil coring. Soil chemical characteristics and moisture were analyzed for all of the three altitudinal levels and depth classes. The annual fine root production of the species was calculated based on min-max method. Fine root production increased markedly from 3270 kg. ha-1. yr-1 at 3000 masl and 2850 kg. ha-1. yr-1 at 3300 masl to 9987 kg. ha-1. yr-1 at 3500 masl. Total nitrogen, available phosphorous, organic carbon, moisture content and PH of the soil increased significantly as altitude increased. In the two lower altitudinal levels, 3000 and 3300masl, fine root mass and biomass decreased as depth increased, but at the higher altitude (3500 masl) fine root tended to more concentrated at the deeper depths while the availability of soil nutrient and soil acidity showed a tendency to decreased as depth increased at all of the three sites. The highest fine root mass and biomass was recorded at the major rainy season followed by the transition period, the small rainy and dry period, in that order. The highest fine root mass during the major rainy season and lowest fine root mass in the dry season indicated that soil moisture was critical factor in governing the pattern of root growth in this ecosystem.